DESIGNING COURSE AND SYLLABUS OF COLLABORATIVE ENGLISH TEACHING: ADDRESSING THE NEEDS OF PHYSICS STUDENTS AT BRAWIJAYA UNIVERSITY - IIS NUR RODLIYAH, M.Ed (Jurnal Humanitas)
This paper discusses an instance of an English course design which is developed based on students’ needs. The program is designed as ESP for Physic students of Brawijaya University, Indonesia. This is a collaborative program in teaching English which involves not only English instructors but also lecturers of Physics Study Program. The collaboration is conducted in designing the course, selecting materials as well as implementing the materials in the classroom. In brief, collaborative teaching can be adopted as a good design for teaching ESP for students of non English Departments as the collaboration makes the course designing job fruitful.